The Influence of Employee Competence on Employee Performance in The Department of Women's Empowerment, Child Protection and Community of Binjai City - Azizah, Lailan; Isa Indrawan, Muhammad (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
The aim of this research is to determine and analyze the influence of competency on employee performance at the Binjai City Women's Empowerment, Child Protection and Community Office. This research was conducted using a causal associative quantitative approach. The sample used was all employees with a total of 61 people. The results of the analysis show that competency has a significant influence on employee performance (T-statistic 2,924 > 1.670; P-value 0.005 < 0.05), which indicates that increasing competency directly increases employee performance. The result of the Adjusted R Square value is 0.112 or 11.20%, which means that employee competency has a low influence on employee performance, while the remaining 88.80% is influenced by other factors that have not been studied. This finding provides insight into the relationship between competency and performance, emphasizing the importance of competency in improving employee performance.